2013
DOI: 10.12691/ajmbr-1-4-6
|View full text |Cite
|
Sign up to set email alerts
|

Growth Dynamics of CD4 cells in HIV-1 Patients on Antiretroviral Therapy (ART) at the Builsa District Hospital in Ghana

Abstract: The monitoring of CD4 counts are a basis for assessing the effectiveness of most HIV treatments. Understanding the way CD4 cells change over time among patients on ART could provide insight into the way Patients respond to treatment and how effective treatment is with time. This study examine the changes in CD4 countover time and the effect of some plausible factors on this change for Patients who were on Antiretroviral Therapy(ART) in The Builsa District Hospital in Ghana. Retrospective data from the HIV/AIDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
4
1
0
Order By: Relevance
“…Accordingly, the CD4+ gain attained by younger (<25 years) patients was +66 cells/mm 3 as compared to those older than 45 years of age (β = −66.19, 95% CI [−126.68,−5.70], P = 0.032). The finding is consistent with the studies from Asia [ 19 ] and Ghana [ 29 ] and which reported the inverse relationship between age and CD4+ gain. This is mainly due to failure of cellular expansion or non-sustained cell survival in the periphery or age related central degeneration of thymus function as patients become older [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Accordingly, the CD4+ gain attained by younger (<25 years) patients was +66 cells/mm 3 as compared to those older than 45 years of age (β = −66.19, 95% CI [−126.68,−5.70], P = 0.032). The finding is consistent with the studies from Asia [ 19 ] and Ghana [ 29 ] and which reported the inverse relationship between age and CD4+ gain. This is mainly due to failure of cellular expansion or non-sustained cell survival in the periphery or age related central degeneration of thymus function as patients become older [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…So, a patient has a 0.879 CD4+ cell count advantage over time, for every count higher in initial CD4+ count, when compared to his/her counterpart ( B = 0.879 95% CI [0.70, 1.06] , P < 0.001). This finding is consistent form study by Lawrence et al [ 27 ] and Mustapha et al [ 29 ] in which higher baseline CD4+ count was associated with good immunologic outcome. This might be due to less extensively depleted immune system will be boosted easily after initiation of ART.…”
Section: Discussionsupporting
confidence: 92%
“…erefore, each unit increment in the baseline CD4+ count will contribute to 0.55 cells/mm 3 CD4 gain every half year (β = 0.55, 95% CI [0.49-0.69]). is is concurrent with previous studies [31][32][33][34], in which a higher baseline CD4+ lymphocyte count was associated with better immunologic response. is could be due to less extensively depleted immune system, which will be boosted easily after initiation of ART.…”
Section: Discussionsupporting
confidence: 90%
“…Figure 5 indicates that as age of patients increased, the rate of reduction of adherence level was more rapid for patients who lived in the rural areas than in urban areas. Consistent with the results from the recent longitudinal studies, the findings in this study showed that adherence to HAART progression improved through time (Luguterah and Adams, 2013). This indicates that the interventions on program might have had a positive effect on patients' adherence to HAART.…”
Section: Interactional Effects Between Age and Residence Area Of Patisupporting
confidence: 91%
“…Patients with poor adherence to HAART in this longterm treatment program were at risk and interventions should target these groups. Patients should initiate HAART early enough to reduce mortality, morbidity and HIV transmission (Adams and Luguterah, 2013;Asfaw et al, 2015). Single intervention strategy cannot improve risks of patients with non-adherent to HAART.…”
Section: The Way Forwardmentioning
confidence: 99%